(untitled) (Commonwealth Journal of Local Governance, 2015)
For more than 100 years, non-landed and non-Establishment interests in rural England were represented by a succession of three quasi-independent government bodies (quangos). These were the Development/Rural Development Commissions, the Countryside Agency, and the Commission for Rural Communities (CRC). Their roles embraced, to varying degrees, policy, practice, and advocacy. In 2013 the British government closed the CRC and absorbed aspects of its responsibilities into the civil service. The implications of this decision for the disadvantaged people and places of rural England are explored. The potential for land-related interest groups and traditional elites to increase their influence as a consequence, is considered. First, by way of context, the histories of the three quangos and the main interest groups are described. The views of the latter – and others with related interests - were sought (unsuccessfully), together with the opinions of people involved in one or more of the quangos, and, or, the civil service successor unit. These are presented and discussed. Conclusions relating to consequential ‘gaps’ in independent policy and research are drawn. The aim is to stimulate discussion about the implications for rural England of closing the CRC, for it is possible that the loss of this small organization may have unexpected long-term consequences. The eventual significance of this decision has yet to be determined.